Picture the dead - Griffin, Adele (Sourcebooks Fire, 2010)
After Jennie Lovell's fiancé, Will, is killed during the Civil War, she forms an alliance with a spirit photographer and uses her ability to talk to the dead to investigate the secrets Will was hiding and how he really died.